Feasibility of adopting various tools in design phase management for construction projects - Shaliya Mary.J*; Surya Raj Kumar (International Journal of Architectural Design and Planning, 2023)
Managing the design process across the course of a project's lifecycle is known as design phase management. Due to the iterative nature of the design phase, several types of variability affect workflow in construction and present management problems to the project team. In this study, the stakeholders were interviewed in-depth to identify the coordination issues that arise during the design phase of each stage of the building project. Based on background research, the problems were ranked in order of severity. Several tools were found, and decisions were taken on the priority of tools like the last planner system, scrum, and so on. As a result, these tools were provided as a solution at each level of the design process to enhance the coordination issues that arise between the stakeholders during the design phase of the project.
Keywords: coordination problems design phase; design phase management; lean manufacturing; tools and LPS ranking